Chromium-based propane dehydrogenation catalyst with improved catalytic performance, preparation method and application thereof
By using the titanium oxide-Al2O3 composite support in the chromium propane dehydrogenation catalyst, synergistically with elements such as Cr, K, Ni, W, Co, Zn, etc., the low utilization rate of the supported active ingredients and rapid coking of the catalyst in the prior art are solved. The problem of high catalytic performance and long service life have been achieved.
Patent Information
- Application Number
- CN202411347515.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The utilization rate of the existing chromium propane dehydrogenation catalysts on the alumina support is low, resulting in a decrease in the reactivity and selectivity of the catalyst. The catalyst is rapidly coking due to the acid center on the alumina, and traditional modification technology inhibits decomposition. Hydrogen activity increases costs.
The titanium oxide-Al2O3 composite support is used to synergistically interact with elements such as Cr, K, Ni, W, Co, Zn, etc., and the composite support with high specific surface area and uniform pore size is formed by adjusting the component ratio and preparation process, thereby improving the activity and use of the catalyst. life.
The high catalytic performance and long service life of the chromium-based propane dehydrogenation catalyst are achieved, the propylene selectivity and propane conversion rate are improved, and the use amount and cost of active ingredients are reduced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a chromium-based propane dehydrogenation catalyst with improved catalytic performance, a preparation method and an application thereof. Background Art
[0002] Propylene is one of the basic raw materials in the chemical industry and can be used to produce chemical products such as high molecular weight polymers and olefin oxides. The traditional method of producing propylene is to obtain propylene through the catalytic cracking process of petroleum; however, as petroleum resources become increasingly scarce, the traditional production process can no longer meet the rapidly growing demand for propylene, so it is urgent to develop new propylene production technology.
[0003] In the technology of producing propylene by dehydrogenating propane, the performance of the catalyst plays a key role in the yield of propylene, propane conversion rate, propylene selectivity, etc. Regarding chromium-based propane dehydrogenation catalysts, the existing technology mostly adopts the impregnation method to load the active ingredient on the alumina carrier. This method affects the loading amount and dispersion of the active ingredient on the alumina carrier, and the effective utilization rate of the active ingredient is low, thereby reducing the reaction activity and selectivity of the catalyst; and due to the presence of a large number of acid centers on the alumina, the catalyst quickly cokes and olefins crack. Therefore, the catalyst is often modified with alkaline metals or their oxides to reduce the amount of carrier acid, but the above-mentioned modification technology causes a strong interaction between the alkaline oxide and chromium oxide, inhibiting the dehydrogenation activity, resulting in the inability to completely reduce the high-valent chromium, thereby reducing the olefin selectivity.
[0004] Chinese invention patent CN117531500A discloses a propane dehydrogenation catalyst with modified magnesium oxide-alumina as a carrier and a preparation method thereof. The catalyst uses modified magnesium oxide-alumina as a carrier, Cr as an active ingredient, and Na, Zr and W as additives; the carrier contains modified magnesium oxide and active alumina, and the modified magnesium oxide is magnesium oxide modified by Lu and Sc. The invention utilizes Lu and Sc to modify magnesium oxide, which can disperse the catalytic active ingredients and increase the service life of the catalyst. The active ingredient Cr and the additives Na, Zr and W are introduced in appropriate proportions by the impregnation method to improve the selectivity, anti-carbon deposition ability and stability of propylene. However, the Lu element has very few reserves in nature and is relatively expensive; the metal scandium is easily oxidized to form a dark yellow or gray oxide layer, which affects the modified performance of the catalyst.
[0005] Chinese invention patent CN108654596A discloses a propane dehydrogenation catalyst and its preparation method. The catalyst uses chromium composite oxide as the active ingredient, is mixed with a high-performance heat carrier, and a binder and a modifying element are added. It is prepared by kneading, extrusion, drying, and calcination. The mass percentage of each component is: chromium composite oxide 55%-80%, high-performance heat carrier 10%-30%, modifying element 0.1%-10.0% and binder balance. The invention improves the dispersion of chromium on the carrier by synthesizing chromium composite oxide, effectively improves the effective utilization rate of active ingredients and the conversion rate of raw material propane; improves the activity and selectivity of the catalyst by metal modification treatment, thereby improving the propylene yield; and effectively improves the utilization efficiency of the catalyst by adding a high-performance heat carrier. However, the amount of active ingredients and metal elements used in the above technical scheme is relatively large, which increases the cost.
[0006] Based on this, the present invention provides a chromium-based propane dehydrogenation catalyst with improved catalytic performance and a preparation method thereof. Relatively low-priced elements such as Cr, Zr, and W are used to prepare the catalyst. The obtained composite carrier has a large specific surface area, a small pore size, and a uniform size. The active groups of the composite carrier are tightly combined with the active ingredients. A propane dehydrogenation catalyst with high catalytic performance and a long service life can be prepared using a lower content of active ingredients. Summary of the invention
[0007] The present invention aims to solve the problems existing in the prior art and provides a chromium-based propane dehydrogenation catalyst with improved catalytic performance, a preparation method and an application thereof. By adjusting the ratio of Cr, K, Ni, W, Co and Zn, the components work synergistically with each other to promote the catalytic dehydrogenation cycle and improve the catalytic activity. The present invention adopts a composite carrier titanium oxide-Al2O3 with a high specific surface area and uniform pore size, thereby improving the strength of the catalyst and extending the service life of the catalyst.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] Firstly, the present invention provides a chromium-based propane dehydrogenation catalyst with improved catalytic performance, comprising a carrier and an active component loaded on the carrier;
[0010] The carrier is a titanium oxide-Al2O3 composite carrier. The preparation method of the titanium oxide-Al2O3 composite carrier is as follows: tetrabutyl titanate and hexadecyltrimethylammonium bromide (CTAB) are dissolved in isopropanol, and γ-Al2O3 is added to react; then a mixed acid solution of nitric acid and malic acid is added to hydrolyze, and after hydrolysis, the carrier is matured at 30-45°C, dried, and calcined for the first time; the carrier is mixed with starch and extruded, and calcined for the second time;
[0011] The active ingredients contain Cr, K, Ni, W, Co and Zn; Cr is 15wt%-20wt% of the weight of the chromium-based propane dehydrogenation catalyst, K is 0.1wt%-0.3wt% of the weight of the chromium-based propane dehydrogenation catalyst, Ni is 0.8wt%-1.2wt% of the weight of the chromium-based propane dehydrogenation catalyst, W is 0.05wt%-0.2wt% of the weight of the chromium-based propane dehydrogenation catalyst, Co is 0.2wt%-0.4wt% of the weight of the chromium-based propane dehydrogenation catalyst, and Zn is 0.5wt%-0.9wt% of the weight of the chromium-based propane dehydrogenation catalyst.
[0012] Preferably, in the method for preparing the titanium oxide-Al2O3 composite carrier, the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, isopropanol and γ-Al2O3 is 80-120:1-2.5:130-180:100-140.
[0013] Further preferably, in the method for preparing the titanium oxide-Al2O3 composite carrier, the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, isopropanol and γ-Al2O3 is 100:1.5:150:120.
[0014] Preferably, in the preparation of the titanium oxide-Al2O3 composite carrier, the mass ratio of isopropanol to the mixed acid is 130-180:3; further preferably, the mass ratio of isopropanol to the mixed acid is 150:3.
[0015] Preferably, in the method for preparing the titanium oxide-Al2O3 composite carrier, the mass ratio of nitric acid to malic acid is 1:0.4-0.8; further preferably, the mass ratio of nitric acid to malic acid is 1:0.6.
[0016] Preferably, in the method for preparing the titanium oxide-Al2O3 composite carrier, the mass concentration of the mixed acid solution is 0.3wt%-0.5wt%; further preferably, the mass concentration of the mixed acid solution is 0.4wt%.
[0017] Preferably, the specific surface area of the γ-Al2O3 is 300m 2 / g-450m 2 / g.
[0018] Further preferably, the specific surface area of the γ-Al2O3 is 350m 2 / g-400m 2 / g.
[0019] Preferably, in the preparation method of the titanium oxide-Al2O3 composite carrier, the temperature of the first calcination is 750℃-950℃, and the calcination time is 2h-4h; the temperature of the second calcination is 400℃-500℃, and the calcination time is 7h-10h.
[0020] Further preferably, in the preparation method of the titanium oxide-Al2O3 composite carrier, the temperature of the first calcination is 800°C, and the calcination time is 3 hours; the temperature of the second calcination is 450°C, and the calcination time is 8 hours.
[0021] Preferably, in the preparation method of the titanium oxide-Al2O3 composite carrier, the amount of starch added is 0.5%-0.9% of the mass of the titanium oxide-Al2O3 composite carrier; further preferably, the amount of starch added is 0.8% of the mass of the titanium oxide-Al2O3 composite carrier.
[0022] Preferably, the preparation method of the titanium oxide-Al2O3 composite carrier is:
[0023] S1, tetrabutyl titanate and hexadecyltrimethylammonium bromide are dissolved in isopropanol, γ-Al2O3 is added to react for 2h-4h, and then a mixed acid solution of nitric acid and malic acid is added, and the mixture is stirred at 600rpm-1000rpm for hydrolysis for 2h-4h;
[0024] S2, then aging treatment at 30°C-40°C for 12h-18h, drying at 200°C-300°C for 1h-2h and then calcining for the first time to obtain titanium oxide-Al2O3 powder;
[0025] S3. Finally, the titanium oxide-Al2O3 powder is mixed with starch and extruded and then calcined for the second time.
[0026] Further preferably, the preparation method of the titanium oxide-Al2O3 composite carrier is:
[0027] S1, tetrabutyl titanate and hexadecyltrimethylammonium bromide were dissolved in isopropanol, γ-Al2O3 was added to react for 3 h, and then a mixed acid solution of nitric acid and malic acid was added, and the mixture was stirred at 800 rpm for hydrolysis for 3 h;
[0028] S2, then ripening treatment at 35°C for 16h, drying at 250°C for 1.5h and then calcining for the first time to obtain titanium oxide-Al2O3 powder;
[0029] S3. Finally, the titanium oxide-Al2O3 powder is mixed with starch and extruded and then calcined for the second time.
[0030] Preferably, among the active ingredients, Cr is 16wt%-18wt% of the weight of the chromium-based propane dehydrogenation catalyst, K is 0.15wt%-0.25wt% of the weight of the chromium-based propane dehydrogenation catalyst, Ni is 0.9wt%-1.1wt% of the weight of the chromium-based propane dehydrogenation catalyst, W is 0.08wt%-0.15wt% of the weight of the chromium-based propane dehydrogenation catalyst, Co is 0.25wt%-0.35wt% of the weight of the chromium-based propane dehydrogenation catalyst, and Zn is 0.6wt%-0.8wt% of the weight of the chromium-based propane dehydrogenation catalyst.
[0031] Further preferably, among the active ingredients, Cr is 17 wt% of the weight of the chromium-based propane dehydrogenation catalyst, K is 0.2 wt% of the weight of the chromium-based propane dehydrogenation catalyst, Ni is 1 wt% of the weight of the chromium-based propane dehydrogenation catalyst, W is 0.1 wt% of the weight of the chromium-based propane dehydrogenation catalyst, Co is 0.3 wt% of the weight of the chromium-based propane dehydrogenation catalyst, and Zn is 0.7 wt% of the weight of the chromium-based propane dehydrogenation catalyst.
[0032] In the present invention, the source of the active ingredient is not limited to chromium oxide, chromium trioxide, chromium chloride, chromium bromide, chromium nitrate, chromium sulfate, chromium phosphate, potassium hydroxide, nickel nitrate hexahydrate (Ni(NO3)2·6H2O), ammonium metatungstate (H 28 N6O 41 W 12 ), cobalt chloride, cobalt nitrate, zinc chloride, zinc sulfate, zinc phosphate. The present invention does not limit the source of the active ingredient, and all substances containing active ingredients and soluble in water for preparing the catalyst can achieve the technical effect of the present invention.
[0033] Then, the present invention provides a method for preparing the chromium-based propane dehydrogenation catalyst, comprising the steps of:
[0034] (1) Preparation of titanium oxide-Al2O3 composite carrier;
[0035] (2) preparing an impregnation solution: dissolving a substance containing active ingredients of Cr, K, Ni, W, Co and Zn in water to obtain an impregnation solution;
[0036] (3) Impregnation: Place the titanium oxide-Al2O3 composite carrier in the impregnation solution for 0.5h-2h; dry and calcine.
[0037] Preferably, step (1) is specifically as follows: tetrabutyl titanate and hexadecyltrimethylammonium bromide are dissolved in isopropanol, and γ-Al2O3 is added for reaction; then a mixed acid solution of nitric acid and malic acid is added for hydrolysis, and after hydrolysis, the mixture is ripened at 30°C-45°C, dried, and calcined for the first time; and mixed with starch for extrusion and calcined for the second time.
[0038] Further preferably, step (1) is specifically as follows: tetrabutyl titanate and hexadecyltrimethylammonium bromide are dissolved in isopropanol, and γ-Al2O3 is added to react for 2h-4h; then a mixed acid solution of nitric acid and malic acid is added, and hydrolysis is stirred at 600rpm-1000rpm for 2h-4h; then, the mixture is matured at 30℃-40℃ for 12h-18h, and dried at 200℃-300℃ for 1h-2h; a first calcination is performed to obtain titanium oxide-Al2O3 powder; finally, the titanium oxide-Al2O3 powder is mixed with starch and extruded, and a second calcination treatment is performed.
[0039] More preferably, step (1) is specifically as follows: tetrabutyl titanate and hexadecyltrimethylammonium bromide are dissolved in isopropanol, γ-Al2O3 is added to react for 3 hours; then a mixed acid solution of nitric acid and malic acid is added, stirred at 800 rpm for hydrolysis for 3 hours, then ripened at 35°C for 16 hours, and dried at 250°C for 1.5 hours; a first calcination is performed to obtain titanium oxide-Al2O3 powder; finally, the titanium oxide-Al2O3 powder is mixed with starch and extruded, and a second calcination treatment is performed.
[0040] Further preferably, in step (1), the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, isopropyl alcohol and γ-Al2O3 is 80-120:1-2.5:130-180:100-140; further preferably, the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, isopropyl alcohol and γ-Al2O3 is 100:1.5:150:120.
[0041] Further preferably, in step (1), the mass ratio of isopropanol to the mixed acid is 130-180:3; further preferably, the mass ratio of isopropanol to the mixed acid is 150:3.
[0042] Further preferably, in step (1), the mass ratio of nitric acid to malic acid is 1:0.4-0.8; further preferably, the mass ratio of nitric acid to malic acid is 1:0.6.
[0043] Further preferably, in step (1), the mass concentration of the mixed acid solution is 0.3wt%-0.5wt%; further preferably, the mass concentration of the mixed acid solution is 0.4wt%.
[0044] Further preferably, in step (1), the specific surface area of the γ-Al2O3 is 300m 2 / g-450m 2 / g; More preferably, the specific surface area of γ-Al2O3 is 350m 2 / g-400m 2 / g.
[0045] Further preferably, in step (1), the temperature of the first calcination is 750°C-950°C, and the calcination time is 2h-4h; the temperature of the second calcination is 400°C-500°C, and the calcination time is 7h-10h.
[0046] More preferably, in step (1), the temperature of the first calcination is 800° C., and the calcination time is 3 h; the temperature of the second calcination is 450° C., and the calcination time is 8 h.
[0047] Further preferably, in step (1), the amount of starch added is 0.5%-0.9% of the mass of the composite carrier; even more preferably, the amount of starch added is 0.8% of the mass of the composite carrier.
[0048] Preferably, in step (2), the mass ratio of Cr, K, Ni, W, Co and Zn is 15-20:0.1-0.3:0.8-1.2:0.05-0.2:0.2-0.4:0.5-0.9.
[0049] Further preferably, in step (2), the mass ratio of Cr, K, Ni, W, Co and Zn is 16-18:0.15-0.25:0.9-1.1:0.08-0.15:0.25-0.35:0.6-0.8.
[0050] More preferably, in step (2), the mass ratio of Cr, K, Ni, W, Co and Zn is 17:0.2:1:0.1:0.3:0.7.
[0051] Preferably, in the impregnation solution of step (2), the total mass concentration of active ingredients is 5 g / L-15 g / L.
[0052] Further preferably, in the impregnation solution described in step (2), the total mass concentration of active ingredients is 10 g / L.
[0053] Preferably, in step (3), the impregnation is performed by uniformly spraying the impregnation liquid onto the surface of the titanium oxide-Al2O3 composite carrier according to a specific mass ratio of active components to obtain a chromium-based propane dehydrogenation catalyst.
[0054] Preferably, in step (3), the immersion time is 1 hour.
[0055] Preferably, in step (3), the drying conditions are: freeze-drying treatment for 12h-24h; more preferably, freeze-drying treatment for 18h.
[0056] Preferably, in step (3), the calcination is: heating to 600°C-800°C at a rate of 3°C / min-5°C / min and calcining for 2h-4h.
[0057] Further preferably, in step (3), the calcination is: heating to 700° C. at a rate of 34° C. / min and calcining for 3 h.
[0058] Finally, the present invention provides the use of the chromium-based propane dehydrogenation catalyst in the preparation of propylene.
[0059] Preferably, in the application, the process conditions for preparing propylene using a chromium-based propane dehydrogenation catalyst are: a reaction temperature of 500°C-700°C, a reaction pressure of normal pressure, and a space velocity of 700 h -1 -900h -1 .
[0060] Further preferably, in the application, the process conditions for preparing propylene using a chromium-based propane dehydrogenation catalyst are: reaction temperature of 600°C, reaction pressure of normal pressure, and space velocity of 800h -1 .
[0061] The catalytic performance of the chromium-based propane dehydrogenation catalyst is as follows: average pore size 4nm-6nm, average strength 200N-270N, propane conversion rate 40%-55%, propylene selectivity 85%-95%, and propane conversion rate 35%-45% after 10 times of use and regeneration.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] 1. The present invention synthesizes a titanium oxide layer in situ on the surface of Al2O3, which is beneficial to the uniform distribution of titanium oxide on the outer surface of alumina; in the presence of mixed acid and CTAB, the degree of crystallization of titanium oxide is reduced, so that the carrier has a higher specific surface area and uniform pore size, which is more conducive to the loading of active ingredients; the catalyst still has a high catalytic activity when repeatedly used under high temperature conditions.
[0064] 2. The present invention adopts a double calcination method to prepare the titanium oxide-Al2O3 composite carrier. The obtained titanium oxide-Al2O3 composite carrier has uniform pores, which is beneficial to the uniform loading of active components during the impregnation process and reduces the aggregation of active components.
[0065] 3. The present invention uses titanium oxide-Al2O3 material as a carrier and Cr, K, Ni, W, Co, and Zn as electron promoters, which can accelerate the activation of carbon-hydrogen bonds and hydrogen desorption on the titanium oxide covering layer, promote catalytic dehydrogenation cycles, and improve catalytic activity.
[0066] 4. The present invention adjusts the proportion of active ingredients in the impregnation solution: reduces the Cr content in the active ingredients, adds metal additives K, Ni, W, Co and Zn, and each component acts synergistically to improve the catalytic activity. Compared with the traditional chromium-based dehydrogenation catalyst, the chromium-based propane dehydrogenation catalyst prepared by freeze drying in the present invention has both higher catalytic activity and longer service life, and still has a higher propane conversion rate after multiple high-temperature cycles. DETAILED DESCRIPTION
[0067] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0068] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those of ordinary skill in the art to which the present invention belongs.
[0069] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.
[0070] In the following examples, the tetrabutyl titanate was purchased from Sigma-Aldrich, CAS No. 5593-70-4; the hexadecyl trimethyl ammonium bromide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No. 57-09-0; the γ-Al2O3 was purchased from Shandong Wante Co., Ltd.; the activated carbon was columnar activated carbon purchased from Gongyi Shengxing Water Purification Material Factory, with a particle size of 1.5 mm. The above components, products from different manufacturers have no significant effect on the effect.
[0071] Example 1
[0072] A chromium-based propane dehydrogenation catalyst with improved catalytic performance, comprising a carrier and an active component (Cr, K, Ni, W, Co, Zn) supported on the carrier;
[0073] The carrier is a titanium oxide-Al2O3 composite carrier, and the preparation method of the titanium oxide-Al2O3 composite carrier is as follows:
[0074] S1, tetrabutyl titanate and hexadecyltrimethylammonium bromide were dissolved in isopropanol, γ-Al2O3 was added to react for 3 h, and then a mixed acid solution of nitric acid and malic acid was added, and the mixture was stirred at 800 rpm for hydrolysis for 3 h;
[0075] The mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, isopropyl alcohol, γ-Al2O3 and mixed acid is 100:1.5:150:120:3;
[0076] The specific surface area of γ-Al2O3 is 350m 2 / g-400m 2 / g between;
[0077] The mixed acid is a mixture of nitric acid and malic acid, the mass ratio of nitric acid to malic acid is 1:0.6; the mass concentration of the mixed acid solution is 0.4wt%;
[0078] S2, then ripening at 35°C for 16h, removing the solution, drying at 250°C for 1.5h and then calcining for the first time to obtain titanium oxide-Al2O3 powder; the temperature of the first calcination is 800°C and the calcination time is 3h;
[0079] S3, titanium oxide-Al2O3 powder and starch are mixed and extruded, and then calcined for the second time at 450°C for 8h to obtain a titanium oxide-Al2O3 composite carrier; the amount of starch added is 0.8% of the mass of the composite carrier;
[0080] Among the active ingredients, Cr is 17wt% of the weight of the chromium-based propane dehydrogenation catalyst, K is 0.2wt% of the weight of the chromium-based propane dehydrogenation catalyst, Ni is 1wt% of the weight of the chromium-based propane dehydrogenation catalyst, W is 0.1wt% of the weight of the chromium-based propane dehydrogenation catalyst, Co is 0.3wt% of the weight of the chromium-based propane dehydrogenation catalyst, and Zn is 0.7wt% of the weight of the chromium-based propane dehydrogenation catalyst.
[0081] In this embodiment, the preparation method of the chromium-based propane dehydrogenation catalyst is:
[0082] (1) Preparing a titanium oxide-Al2O3 composite carrier according to the above preparation method;
[0083] (2) Preparing an impregnation solution: dissolving chromium trioxide, potassium hydroxide, nickel nitrate hexahydrate, ammonium metatungstate, cobalt nitrate and zinc chloride in water at a mass ratio of Cr:K:Ni:W:Co:Zn=17:0.2:1:0.1:0.3:0.7 to obtain an impregnation solution; the total mass concentration of the active ingredients in the impregnation solution is 10 g / L;
[0084] (3) Impregnation: The titanium oxide-Al2O3 composite carrier was placed in the impregnation solution and impregnated for 1 hour; freeze-dried for 18 hours, heated to 700°C at a rate of 34°C / min, and calcined at 700°C for 3 hours to obtain a chromium-based propane dehydrogenation catalyst (17% Cr; 0.2% K; 1% Ni; 0.1% W; 0.3% Co; 0.7% Zn; 80.7% titanium oxide-Al2O3 composite carrier).
[0085] Example 2
[0086] The difference from Example 1 is that the preparation method of the titanium oxide-Al2O3 composite carrier is different, specifically, step S1 is different:
[0087] S1, tetrabutyl titanate and hexadecyltrimethylammonium bromide were dissolved in isopropanol, γ-Al2O3 was added to react for 4 h, and then a mixed acid solution of nitric acid and malic acid was added, and the mixture was stirred at 1000 rpm for hydrolysis for 2 h;
[0088] The mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, isopropyl alcohol, γ-Al2O3 and mixed acid is 80:1:130:500:3;
[0089] The specific surface area of γ-Al2O3 is 400m 2 / g-450m 2 / g between;
[0090] The mixed acid is a mixture of nitric acid and malic acid, the mass ratio of nitric acid to malic acid is 1:0.4; the mass concentration of the mixed acid solution is 0.3wt%.
[0091] The rest are the same as in Example 1.
[0092] Example 3
[0093] The difference from Example 1 is that the preparation method of the titanium oxide-Al2O3 composite carrier is different, specifically, step S1 is different:
[0094] S1, tetrabutyl titanate and hexadecyltrimethylammonium bromide were dissolved in isopropanol, γ-Al2O3 was added to react for 2 h, and then a mixed acid solution of nitric acid and malic acid was added, and the mixture was stirred at 600 rpm for hydrolysis for 4 h;
[0095] The mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, isopropyl alcohol, γ-Al2O3 and mixed acid is 120:2.5:180:700:3;
[0096] The specific surface area of γ-Al2O3 is 300m 2 / g-350m 2 / g between;
[0097] The mixed acid is a mixture of nitric acid and malic acid, the mass ratio of nitric acid to malic acid is 1:0.8; the mass concentration of the mixed acid solution is 0.5wt%.
[0098] The rest are the same as in Example 1.
[0099] Example 4
[0100] The difference from Example 1 is that the preparation method of the titanium oxide-Al2O3 composite carrier is different, specifically, step S2 and step S3 are different:
[0101] S1, same as in Example 1;
[0102] S2, then ripening treatment at 30°C for 18h, removing the solution, drying at 200°C for 2h and then calcining for the first time to obtain titanium oxide-Al2O3 powder; the temperature of the first calcination is 950°C and the calcination time is 2h;
[0103] S3, titanium oxide-Al2O3 powder and starch are mixed and extruded, and then calcined for the second time at 500°C for 7h to obtain a titanium oxide-Al2O3 composite carrier; the amount of starch added is 0.8% of the mass of the composite carrier.
[0104] The rest are the same as in Example 1.
[0105] Example 5
[0106] The difference from Example 1 is that the preparation method of the titanium oxide-Al2O3 composite carrier is different, specifically, step S2 and step S3 are different:
[0107] S1, same as in Example 1;
[0108] S2, then ripening treatment at 45°C for 12h, removing the solution, drying at 300°C for 1h and then calcining for the first time to obtain titanium oxide-Al2O3 powder; the temperature of the first calcination is 750°C and the calcination time is 4h;
[0109] S3, titanium oxide-Al2O3 powder and starch are mixed and extruded, and then calcined for the second time at 400°C for 10 hours to obtain a titanium oxide-Al2O3 composite carrier; the amount of starch added is 0.8% of the mass of the composite carrier.
[0110] The rest are the same as in Example 1.
[0111] Example 6
[0112] Different from Example 1, in the method for preparing a chromium-based propane dehydrogenation catalyst, the mass ratios of Cr, K, Ni, W, Co and Zn in step (2) are different.
[0113] In step (2) of this embodiment, the mass ratio of Cr, K, Ni, W, Co and Zn is 15:0.3:1.2:0.2:0.4:0.9.
[0114] The rest are the same as in Example 1.
[0115] Example 7
[0116] Different from Example 1, in the method for preparing a chromium-based propane dehydrogenation catalyst, the mass ratios of Cr, K, Ni, W, Co and Zn in step (2) are different.
[0117] In step (2) of this embodiment, the mass ratio of Cr, K, Ni, W, Co and Zn is 20:0.1:0.8:0.05:0.2:0.5.
[0118] The rest are the same as in Example 1.
[0119] Comparative Example 1
[0120] The difference from Example 1 is that the composite carrier is replaced by an activated carbon carrier; the specific surface area of the activated carbon is 850 cm 2 / g or more, particle size 1.5mm.
[0121] The rest are the same as in Example 1.
[0122] Comparative Example 2
[0123] The difference from Example 1 is that the titanium oxide-Al2O3 composite carrier is replaced by a magnesium oxide-Al2O3 composite carrier.
[0124] The preparation method of magnesium oxide-Al2O3 composite carrier is as follows:
[0125] S1. Dissolve hexadecyltrimethylammonium bromide in water, add magnesium oxide and γ-Al2O3, react for 3 hours, add a mixed acid solution of nitric acid and malic acid, and stir at 800 rpm for hydrolysis for 3 hours;
[0126] The mass ratio of hexadecyltrimethylammonium bromide, water, magnesium oxide, γ-Al2O3 and mixed acid is 1.5:150:120:120:3;
[0127] The specific surface area of γ-Al2O3 is 350m 2 / g-400m 2 / g between;
[0128] The mixed acid is a mixture of nitric acid and malic acid, the mass ratio of nitric acid to malic acid is 1:0.6; the mass concentration of the mixed acid solution is 0.4wt%;
[0129] S2, then ripening at 35°C for 16h, removing the solution, drying at 250°C for 1.5h and then calcining for the first time to obtain magnesium oxide-Al2O3 powder; the temperature of the first calcination is 800°C, and the calcination time is 3h;
[0130] S3, magnesium oxide-Al2O3 powder and starch are mixed and extruded, and then calcined for the second time at 450°C for 8h to obtain a magnesium oxide-Al2O3 composite carrier; the amount of starch added is 0.8% of the mass of the composite carrier.
[0131] The rest are the same as in Example 1.
[0132] Comparative Example 3
[0133] The difference from Example 1 is that CTAB (hexadecyltrimethylammonium bromide) in step S1 is replaced by polyethylene glycol 600. The rest is the same as Example 1.
[0134] Comparative Example 4
[0135] Different from Example 1, in the preparation method of the titanium oxide-Al2O3 composite carrier, the calcination method is only one time. Specifically:
[0136] S1, same as in Example 1;
[0137] S2. Then, the mixture was matured at 35°C for 16 hours, the solution was removed, mixed with starch and extruded, and then calcined. After calcination at 450°C for 8 hours, a titanium oxide-Al2O3 composite carrier was obtained; the amount of starch added was 0.8% of the mass of the composite carrier.
[0138] The rest are the same as in Example 1.
[0139] Comparative Example 5
[0140] Different from Example 1, in the preparation method of the titanium oxide-Al2O3 composite carrier, the maturation treatment of step S2 is different, specifically:
[0141] S1, same as in Example 1;
[0142] S2, then ripening at 60°C for 16h, removing the solution, drying at 250°C for 1.5h and then calcining for the first time to obtain titanium oxide-Al2O3 powder; the temperature of the first calcination is 800°C, and the calcination time is 3h;
[0143] S3. Same as Example 1.
[0144] The rest are the same as in Example 1.
[0145] Comparative Example 6
[0146] The difference from Example 1 is that the active ingredients in the impregnation solution are different, namely, Cr, K and W.
[0147] The preparation method of the chromium propane dehydrogenation catalyst is as follows:
[0148] (1) Same as Example 1;
[0149] (2) preparing an impregnation solution: dissolving chromium trioxide, potassium hydroxide and ammonium metatungstate in water at a mass ratio of Cr:K:W=17:0.2:0.1 to obtain an impregnation solution; the total mass concentration of the active ingredients in the impregnation solution is 10 g / L;
[0150] (3) Impregnation: The titanium oxide-Al2O3 composite carrier was placed in the impregnation solution and impregnated for 1 hour; freeze-dried for 18 hours, heated to 700°C at a rate of 34°C / min, and calcined at 700°C for 3 hours to obtain a chromium-based propane dehydrogenation catalyst (18.97% Cr; 0.22% K; 0.11% W; 80.7% titanium oxide-Al2O3 composite carrier).
[0151] Comparative Example 7
[0152] The difference from Example 1 is that the active ingredients in the impregnation solution are different, namely Ni, Co and Zn.
[0153] The preparation method of the chromium propane dehydrogenation catalyst is as follows:
[0154] (1) Same as Example 1;
[0155] (2) preparing an impregnation solution: dissolving nickel nitrate hexahydrate, cobalt nitrate and zinc chloride in water at a mass ratio of Ni:Co:Zn=1:0.3:0.7 to obtain an impregnation solution; the total mass concentration of the active ingredients in the impregnation solution is 10 g / L;
[0156] (3) Impregnation: The titanium oxide-Al2O3 composite carrier was placed in the impregnation solution and impregnated for 1 hour; freeze-dried for 18 hours, heated to 700°C at a rate of 34°C / min, and calcined at 700°C for 3 hours to obtain a chromium-based propane dehydrogenation catalyst (9.6% Ni; 2.9% Co; 6.8% Zn; 80.7% titanium oxide-Al2O3 composite carrier).
[0157] Comparative Example 8
[0158] Different from Example 1, in the preparation method of the chromium-based propane dehydrogenation catalyst, the drying method of step (3) is different: freeze drying for 18 hours is replaced by drying at 100° C. for 8 hours.
[0159] The remaining steps are the same as those in Example 1.
[0160] Comparative Example 9
[0161] The catalyst was prepared according to Example 1 of Chinese invention patent CN117531500A.
[0162] (1) Add 37.69g Lu(NO3)3·6H2O and 13.40g Sc(NO3)3·6H2O to 100mL water to prepare a mixed solution, add 90g MgO to the mixed solution, soak for 6h, take out the impregnated MgO, place it in an oven, and dry it at a constant temperature of 150℃ for 3.5h, then calcine the dried solid at 500℃ for 6h to obtain Lu and Sc modified magnesium oxide. Then take 15g of the prepared Lu and Sc modified magnesium oxide, 85g of activated alumina and sesbania powder, stir and mix them thoroughly, and extrude them in a single screw extruder to obtain the Lu and Sc modified magnesium oxide-alumina mixed metal oxide as a catalyst carrier for standby use.
[0163] (2) Dissolve 28.85 g of chromium trioxide, 0.87 g of sodium hydroxide, 1.86 g of zirconium nitrate, and 0.15 g of ammonium metatungstate in 50 mL of water to obtain a mixed solution; immerse the catalyst carrier in the mixed solution for 10 h, dry it in an oven at 120° C. for 4 h, and calcine it in a muffle furnace at 600° C. for 3 h to obtain a chromium-based propane dehydrogenation to propylene catalyst.
[0164] Test 1: Catalyst physical property testing
[0165] The average pore diameter and strength of the propane dehydrogenation catalysts prepared in Examples 1 to 5, Comparative Example 1, Comparative Example 2, Comparative Example 4, Comparative Example 5, Comparative Example 8 and Comparative Example 9 were tested respectively.
[0166] The pore size of the propane dehydrogenation catalyst was measured using an ASAP 2460 fully automatic specific surface and pore size analyzer produced by American Minionomeritics Instruments. The test was repeated 5 times, and the average pore size results are shown in Table 1.
[0167] The crushing strength of propane dehydrogenation catalyst particles was measured using a ZQJ-Ⅱ intelligent particle strength testing machine. The number of test samples was 50, and the results were averaged. The average strength of the propane dehydrogenation catalyst is shown in Table 1.
[0168] Table 1
[0169]
[0170] In Table 1, each comparative example is compared with Example 1. # P≤0.05, ## P≤0.01.
[0171] As can be seen from Table 1, the propane dehydrogenation catalyst prepared by the preparation method of the present invention has a smaller and more uniform pore size than the propane dehydrogenation catalyst of the comparative example, which is beneficial to the loading of active components and avoids the aggregation of active components, thereby improving the catalytic effect of the catalyst.
[0172] In addition, the preparation method of the present invention adopts a specific maturation and gradient temperature calcination treatment process to form pores of uniform size, thereby improving the strength of the catalyst; avoiding the phenomenon of easy cracking and crushing of the catalyst carrier during use, thereby extending the service life of the catalyst.
[0173] Test 2 Catalytic performance test
[0174] The propane dehydrogenation reaction to produce propylene was carried out in a fixed bed reactor at a reaction temperature of 600°C, a reaction pressure of atmospheric pressure, and a reaction gas composition of propane: nitrogen = 9:1; the space velocity was 800 h -1 , propane dehydrogenation catalyst loading amount 5g. The reaction gas was passed into the reactor loaded with the above catalyst for 5 hours to obtain the product, and the product was analyzed by GC 7900 gas chromatograph. The results of propane conversion and propylene selectivity after 5 hours of reaction are shown in Table 2;
[0175] The propane dehydrogenation catalyst participating in the reaction was regenerated, and after the reaction was repeated 10 times, the propane conversion rate after regeneration was tested. The results are shown in Table 2.
[0176] Table 2
[0177]
[0178] In Table 2, each comparative example is compared with Example 1. # P≤0.05, ## P≤0.01.
[0179] As can be seen from Table 2, the propane dehydrogenation catalyst prepared by the preparation method of the embodiment of the present invention has a higher catalytic effect than the propane dehydrogenation catalyst of the comparative example, and the propane conversion rate and propylene selectivity are significantly improved; the catalyst has a long service life. In the propane dehydrogenation reaction to propylene, with 5 hours as a reaction unit, after 10 consecutive regeneration reactions, it still has a relatively high propane conversion rate.
[0180] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A chromium-based propane dehydrogenation catalyst with improved catalytic performance, characterized in that: comprising a carrier and an active ingredient loaded on the carrier; The carrier is a titanium oxide-Al2O3 composite carrier. The preparation method of the titanium oxide-Al2O3 composite carrier is as follows: tetrabutyl titanate and hexadecyltrimethylammonium bromide are dissolved in isopropyl alcohol, and γ-Al2O3 is added to react; then a mixed acid solution of nitric acid and malic acid is added to hydrolyze, and after hydrolysis, the composite carrier is subjected to a ripening treatment at 30°C-45°C, dried, and calcined for the first time; the composite carrier is mixed with starch and extruded, and calcined for the second time; the first calcination temperature is 750°C-950°C, and the calcination time is 2h-4h; the second calcination temperature is 400°C-500°C, and the calcination time is 7h-10h; The active components contain Cr, K, Ni, W, Co and Zn; Cr accounts for 15wt%-20wt% of the weight of the chromium-based propane dehydrogenation catalyst, K accounts for 0.1wt%-0.3wt% of the weight of the chromium-based propane dehydrogenation catalyst, Ni accounts for 0.8wt%-1.2wt% of the weight of the chromium-based propane dehydrogenation catalyst, W accounts for 0.05wt%-0.2wt% of the weight of the chromium-based propane dehydrogenation catalyst, Co accounts for 0.2wt%-0.4wt% of the weight of the chromium-based propane dehydrogenation catalyst, and Zn accounts for 0.5wt%-0.9wt% of the weight of the chromium-based propane dehydrogenation catalyst.
2. The chromium-based propane dehydrogenation catalyst according to claim 1, characterized in that In the preparation method of the titanium oxide-Al2O3 composite carrier, the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, isopropyl alcohol and γ-Al2O3 is 80-120:1-2.5:130-180:100-140; the mass ratio of isopropyl alcohol to mixed acid is 130-180:3; the mass ratio of nitric acid to malic acid is 1:0.4-0.8; the mass concentration of the mixed acid solution is 0.3wt%-0.5wt%; the specific surface area of γ-Al2O3 is 300m 2 / g-450m 2 / g.
3. The chromium-based propane dehydrogenation catalyst according to claim 2, characterized in that In the preparation method of the titanium oxide-Al2O3 composite carrier, the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, isopropyl alcohol and γ-Al2O3 is 100:1.5:150:120; the mass ratio of isopropyl alcohol to mixed acid is 150:3; the mass ratio of nitric acid to malic acid is 1:0.6; the mass concentration of the mixed acid solution is 0.4wt%; the specific surface area of γ-Al2O3 is 350m 2 / g-400m 2 / g.
4. The chromium-based propane dehydrogenation catalyst according to claim 1, characterized in that In the preparation method of the titanium oxide-Al2O3 composite carrier, the added amount of starch is 0.5%-0.9% of the mass of the titanium oxide-Al2O3 composite carrier.
5. The chromium-based propane dehydrogenation catalyst according to claim 4, characterized in that In the preparation method of the titanium oxide-Al2O3 composite carrier, the first calcination temperature is 800°C and the calcination time is 3 hours; the second calcination temperature is 450°C and the calcination time is 8 hours.
6. The chromium-based propane dehydrogenation catalyst according to claim 1, characterized in that The preparation method of the titanium oxide-Al2O3 composite carrier is as follows: S1, tetrabutyl titanate and hexadecyltrimethylammonium bromide were dissolved in isopropyl alcohol, γ-Al2O3 was added and reacted for 2h-4h, and then a mixed acid solution of nitric acid and malic acid was added and stirred at 600rpm-1000rpm for hydrolysis for 2h-4h; S2, then aging treatment at 30-40 ° C for 12 hours to 18 hours, drying at 200-300 ° C for 1 hour to 2 hours, and then calcining for the first time to obtain titanium oxide-Al2O3 powder; S3. Finally, the titanium oxide-Al2O3 powder is mixed with starch and extruded and then calcined for the second time.
7. The chromium-based propane dehydrogenation catalyst according to claim 1, characterized in that Among the active ingredients, Cr accounts for 16wt%-18wt% of the weight of the chromium-based propane dehydrogenation catalyst, K accounts for 0.15wt%-0.25wt% of the weight of the chromium-based propane dehydrogenation catalyst, Ni accounts for 0.9wt%-1.1wt% of the weight of the chromium-based propane dehydrogenation catalyst, W accounts for 0.08wt%-0.15wt% of the weight of the chromium-based propane dehydrogenation catalyst, Co accounts for 0.25wt%-0.35wt% of the weight of the chromium-based propane dehydrogenation catalyst, and Zn accounts for 0.6wt%-0.8wt% of the weight of the chromium-based propane dehydrogenation catalyst.
8. The method for preparing the chromium-based propane dehydrogenation catalyst according to any one of claims 1 to 7, characterized in that: Including steps: (1) Preparation of titanium oxide-Al2O3 composite support; (2) Preparing an impregnation solution: dissolving a substance containing active ingredients of Cr, K, Ni, W, Co, and Zn in water to obtain an impregnation solution; (3) Impregnation: Place the titanium oxide-Al2O3 composite carrier in the impregnation solution for 0.5h-2h; freeze-dry for 12h-24h and calcine to obtain a chromium-based propane dehydrogenation catalyst.
9. The preparation method according to claim 8, characterized in that In step (2), the mass ratio of Cr, K, Ni, W, Co and Zn is 15-20:0.1-0.3:0.8-1.2:0.05-0.2:0.2-0.4:0.5-0.9; In step (3), the calcination is as follows: heating to 600°C-800°C at a rate of 3°C / min-5°C / min and calcining for 2h-4h.
10. Use of the chromium-based propane dehydrogenation catalyst according to any one of claims 1 to 7 in the preparation of propylene.
Citation Information
Cited By
Preparation method and application of a propane dehydrogenation catalyst
CN120037898B
